2017
DOI: 10.1002/slct.201700459
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Trace‐Level Ammonia Gas Sensor Based on Surface‐Engineered Ag Nanoclusters@Polyaniline/Multiwalled Carbon Nanotubes and Insights into Their Mechanistic Pathways

Abstract: An ultrasensitive and selective chemiresistive sensor interface based on Ag nanocluster integrated polyaniline functionalized multi-walled carbon nanotubes (AgNC@PANI/MWCNTs) has been developed for trace-level detection of NH 3 gas at room temperature. AgNC@PANI/MWCNTs was synthesized using surfactant-free, one-pot wet-chemical process, by controlled integration of active Ag sites onto MWCNTs. The structure and morphology of AgNC@PANI/MWCNTs nanocomposite have been extensively studied by various characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…It is worthy to mention that the sensors containing Pt/MWCNT are better for the NH 3 detection than these made with Pd/MWCNT because their response time are lower, compare their response time at room temperature in Table 2. According to Abdulla et al [22], the high binding energy (E b ) between the ammonia gas molecules, the defects present on the MWCNTs surface, and the absorbed oxygen could considerably increase the recovery time of the sensor at room temperatures. Furthermore, Van et al [18] found that composites of SnO 2 /MWCNTs increase their sensitivity for the detection of the ammonia gas when high operating temperatures are employed, since this causes the desorption of the gas molecules from the surface of the MWCNTs.…”
Section: Results Of the Sensitivity Measurement Of The Chrsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worthy to mention that the sensors containing Pt/MWCNT are better for the NH 3 detection than these made with Pd/MWCNT because their response time are lower, compare their response time at room temperature in Table 2. According to Abdulla et al [22], the high binding energy (E b ) between the ammonia gas molecules, the defects present on the MWCNTs surface, and the absorbed oxygen could considerably increase the recovery time of the sensor at room temperatures. Furthermore, Van et al [18] found that composites of SnO 2 /MWCNTs increase their sensitivity for the detection of the ammonia gas when high operating temperatures are employed, since this causes the desorption of the gas molecules from the surface of the MWCNTs.…”
Section: Results Of the Sensitivity Measurement Of The Chrsmentioning
confidence: 99%
“…MWCNTs decorated with Pt-Ag NPs showed up to 5% more sensitivity than the MWCNTs without NPs, which have only 1.5%. Nanoparticles such as Au, Pt [15][16][17] SnO 2 [18], Ag [14,19], Co [20], ITO [21], Ag/ polyaniline [22] Pd [23] and CdS [10] have been also used on MWCNTs, for ammonia gas detection. So far, techniques such as electron beam evaporation, plasma treatment, sputtering coating, precipitation from the metal salt solution, and thermal evaporation have been employed to decorate MWCNTs [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The creation of various composites based on MWCNTs, a matrix of conducting polymers (e.g., poly(3,4-ethylenedioxythiophene)–polystyrene sulfonic acid [ 134 ], polyaniline [ 135 , 136 ], polythiothene [ 137 ], etc. ), and metal oxides (TiO 2 [ 138 ], Al 2 O 3 [ 139 ]) made it possible to significantly improve the sensing behavior toward ammonia.…”
Section: Gas Sensors Based On Carbon Nanotubesmentioning
confidence: 99%
“…Ammonia (NH3) is a hazardous, colorless gas and is widely used in industry, agriculture, and breeding. In the human breath, NH3 concentration is in the range of 50-2000 ppb and could be used as an indicator of kidney, liver dysfunctions as well as stomach diseases [1]. Nowadays, most of the NH3 gas sensor are conductometric sensors and are based on metal oxide semiconductors such as SnO2, WO3, ... which have high working temperatures (normally higher than 200°C) [2].…”
Section: Introductionmentioning
confidence: 99%